2011
DOI: 10.3402/qhw.v6i3.7254
|View full text |Cite
|
Sign up to set email alerts
|

‘They don't understand…you cut yourself in order to live.’ Interpretative repertoires jointly constructing interactions between adult women who self-harm and professional caregivers.

Abstract: The aim of the study was to illuminate interpretative repertoires that jointly construct the interaction between adult women who self-harm and professional caregivers in psychiatric inpatient care. Participant observations and informal interviews were conducted among six women who self-harm and their professional caregivers in two psychiatric inpatient wards, and analysed using the concept of interpretative repertoires from the discipline of discursive psychology. The analysis revealed four interpretative repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Inpatients expect an environment to recover in, with support and help, including relationships, access to information, enhanced communication, a place of safety and personal space, activities, medication and a chance to be involved in treatment planning (Lindgren,Öster,Åström, & Graneheim, 2011;Lindgren, Wilstrand, Gilje, & Olofsson, 2004;Walsh & Boyle, 2009). Nursing staff report dissatisfaction with their work milieu and with their knowledge of best inpatient care practice for people with mental ill-health (Seed, Torkelson, & Alnatour, 2010;Wilstrand et al, 2007).…”
mentioning
confidence: 99%
“…Inpatients expect an environment to recover in, with support and help, including relationships, access to information, enhanced communication, a place of safety and personal space, activities, medication and a chance to be involved in treatment planning (Lindgren,Öster,Åström, & Graneheim, 2011;Lindgren, Wilstrand, Gilje, & Olofsson, 2004;Walsh & Boyle, 2009). Nursing staff report dissatisfaction with their work milieu and with their knowledge of best inpatient care practice for people with mental ill-health (Seed, Torkelson, & Alnatour, 2010;Wilstrand et al, 2007).…”
mentioning
confidence: 99%
“…For example, such approaches can involve practices including providing advice on wound‐hygiene, or supplying sterile cutting blades, activities which have no direct corollaries in terms of the management of, say, aggression. Nevertheless, there has been a growing interest in harm‐minimization approaches for self‐injury, and such techniques have been advocated by some who suggest that a more baldly preventative approach can be distressing, stigmatizing and detrimental to the therapeutic relationship with professionals, and can contribute to behavioural escalation (Duperouzel & Fish, ; Holley, Horton, Cartmail, & Bradley, ; Lindgren, Öster, Åström, & Graneheim, ; Pembroke, ; Shaw, ). Much debate around the use of harm‐minimization approaches has been rooted in non‐empirical discussions of ethics and legalities, much of whose tone suggests a stark binary choice between adopting or proscribing such techniques (e.g., Edwards & Hewitt, ; Gutridge, ; Sullivan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Observing the interactions between women who self‐harmed and professional caregivers, Lindgren et al . () found that the caregivers usually took on either a fostering or a supportive role, and the women who self‐harmed mainly took on the roles of victims or experts. When caregivers were supportive and acknowledged the women as experts, listened to them, and believed in their expertise based on experience, the women were more satisfied with their care.…”
Section: Introductionmentioning
confidence: 99%
“…, Lindgren et al . ) because people who self‐harm experience the behaviour as their only possible way to survive (Lindgren et al . , Brown & Kimball ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation